Nigeria : Second Review Under the Policy Support Instrument-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Nigeria. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Second Review Under the Policy Support Instrument for Nigeria. All assessment criteria through end-September were met except for one civil service-related measure. Remedial measures have prevented the civil service reform program from being compromised. Four structural benchmarks, including two privatizations, were delayed. Against the backdrop of improved macroeconomic performance and large oil wealth, focus is on achieving the Millennium Development Goals including through increased infrastructure spending. Targeted spending in the Niger Delta could help restore stability and boost Nigeria's economic growth.